Solve for y -9y-13=-103

Math
-9y-13=-103
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 13 to both sides of the equation.
-9y=-103+13
Add -103 and 13.
-9y=-90
-9y=-90
Divide each term by -9 and simplify.
Tap for more steps…
Divide each term in -9y=-90 by -9.
-9y-9=-90-9
Cancel the common factor of -9.
Tap for more steps…
Cancel the common factor.
-9y-9=-90-9
Divide y by 1.
y=-90-9
y=-90-9
Divide -90 by -9.
y=10
y=10
Solve for y -9y-13=-103

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top